Total Endovascular Debranching of the Aortic Arch - Yoshida, R. A. [UNESP]; Kolvenbach, R.; Yoshida, W. B. [UNESP]; Wassijew, S.; Schwierz, E.; Lin, F. (W B Saunders Co Ltd, 2011)
Background: Significant morbidity and mortality are related to conventional aortic replacement surgery. Endovascular debranching techniques, fenestrated or branched endografts are time consuming and costly.Objective: We alternatively propose to use endovascular approach with parallel grafts for debranching of aortic arch.Methods: Under general anesthesia, 12 F sheaths were inserted in the femoral, axillary and common carotid arteries for vascular accesses. ViaBahn grafts 10 - 15 cm in length were placed into the aortic arch from right common carotid, left common carotid and left axillary arteries, until the tip of each graft reached into the ascending aorta. Through one femoral artery, the aortic stent-graft was positioned and delivered. Soon after, the parallel grafts were sequentially delivered. Self-spanding Wallstents(R) were used for parallel grafts reinforcement. Ballooning was routinely used for parallel grafts and rarely for aortic graft.Results: This technique was used in 2 cases. The first one was a lady with 72 years old, with an aortic retrograde dissection from left subclavian artery and involving remaining arch branches. Through right common carotid artery a stent-graft was placed in the ascending aorta and through the left common carotid artery a ViaBahn was inserted parallel to the former. A thoracic endograft then covered all the aortic arch dissection extending into the ascending aorta close to the sinu-tubular junction. The second case was a 82 year old male patient with a 7 cm aortic arch aneurysm. Through both common carotid arteries ViaBahn grafts were introduced and positioned into the ascending aorta. Soon after, the deployment of the thoracic stent graft covered all parallel grafts of the aortic arch, excluding the aneurysm. Both cases did not have neurologic or cardiac complications and were discharged 10 days after the procedure.Conclusions: This technique may be a good minimal invasive off-the-shelf technical option for aortic arch "debranching". More data and further improvements are required before this promising technique can be widely advocated. (C) 2011 European Society for Vascular Surgery. Published by Elsevier Ltd. All rights reserved.
Keywords: Aortic aneurysm; Aneurysm dissecting; Surgery; Endovascular procedures; Research and new techniques; Prostheses and implants